Increased Risk for Meningococcal Disease Among Men Who Have Sex With Men in the United States, 2012–2015. (13th May 2017) - Folaranmi, Temitope A; Kretz, Cecilia B; Kamiya, Hajime; MacNeil, Jessica R; Whaley, Melissa J; Blain, Amy; Antwi, Mike; Dorsinville, Marie; Pacilli, Massimo; Smith, Shamika; Civen, Rachel; Ngo, Van; et al.
Summary: Although overall incidence is low, MSM are at increased risk of meningococcal disease compared to men not known to be MSM (non-MSM). HIV infection may play a key role in this increased risk. Abstract: Background: Several clusters of serogroup C meningococcal disease among men who have sex with men (MSM) have been reported in the United States in recent years. The epidemiology and risk of meningococcal disease among MSM is not well described. Methods: All meningococcal disease cases among men aged 18–64 years reported to the National Notifiable Disease Surveillance System between January 2012 and June 2015 were reviewed. Characteristics of meningococcal disease cases among MSM and men not known to be MSM (non-MSM) were described. Annualized incidence rates among MSM and non-MSM were compared through calculation of the relative risk and 95% confidence intervals. Isolates from meningococcal disease cases among MSM were characterized using standard microbiological methods and whole-genome sequencing. Results: Seventy-four cases of meningococcal disease were reported among MSM and 453 among non-MSM. Annualized incidence of meningococcal disease among MSM was 0.56 cases per 100000 population, compared to 0.14 among non-MSM, for a relative risk of 4.0 (95% confidence interval [CI], 3.1–5.1). Among the 64 MSM with known status, 38 (59%) were infected with human immunodeficiency virus (HIV). HIV-infected MSM had 10.1 times (95% CI, 6.1–16.6) the risk of HIV-uninfected MSM. All isolates from cluster-associated cases were serogroup C sequence type 11. Conclusions: MSM are at increased risk for meningococcal disease, although the incidence of disease remains low. HIV infection may be an important factor for this increased risk. Routine vaccination of HIV-infected persons with a quadrivalent meningococcal conjugate vaccine in accordance with Advisory Committee on Immunization Practices recommendations should be encouraged.